Physical interactions between cupuassu and cocoa fats - S. C. S. Lannes; M. L. Medeiros; L. A. Gioielli (Grasas y Aceites, 2003)
Cupuassu (Theobroma grandiflorum, Sterculiaceae) is an Amazonian native fruit and nowadays is cultivated only in Amazonian region. The seeds that come to about 16% of the dry weight can be used to derive a cocoa butter like product and the content of fat in the seeds is about 60% dry weight. In general, these fats are similar to those of cocoa, although they show difference in some physical properties. The objective of this study was to analyse some physical and crystallization properties of the cupuassu fat, cocoa butter and some mixtures between the two fats. The analyses performed were: dropping point, solid fat content, hardness index and Jensen cooling curve. The results suggested some advantages of the use of cupuassu fat, as lower crystallization time and smoothness than cocoa butter. The mixtures showed compatibility, cocoa butter showed bigger solid fat content at room temperature than cupuassu fat and the mixtures. Cupuassu fat had a lower dropping point than cocoa butter. The possible use of cupuassu fat and the mixtures could be in fillings and cold weather chocolate products